a= -1
2007-01-04 13:08:52
·
answer #1
·
answered by symperl 2
·
0⤊
0⤋
a+(-7)+8
=a-7+8
=a+1
2007-01-04 17:13:41
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
First: the expression can also be written as (a - 7 + 8) in which, the negative/subtraction sign dominates.
a - 7 + 8
Sec: solve > combine "like" terms > -7 + 8
a + 1
2007-01-04 12:59:29
·
answer #3
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
a=15
2007-01-04 12:32:31
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Hmm, I will assume you mean a + (-7) = 8, which would mean a = 15.
2007-01-04 12:25:44
·
answer #5
·
answered by JasonM 7
·
0⤊
0⤋
a-7+8
=a+1simplified form
if youequate it to zero
a=-1
2007-01-04 12:26:27
·
answer #6
·
answered by raj 7
·
0⤊
0⤋
The only thing I can see to do is simplifiy it, which would be a + 1
2007-01-04 12:26:42
·
answer #7
·
answered by Me 2
·
0⤊
0⤋
me is right
a+(-7)+8
a-7+8
a+1
2007-01-04 12:34:20
·
answer #8
·
answered by kain_odeh 2
·
0⤊
0⤋
no thank you
2007-01-04 12:25:57
·
answer #9
·
answered by Anonymous
·
0⤊
2⤋